Occupational Health Hazards in Sanitary Workers of Chandrapur City, Central India - Patil, Priyanka V.; Kamble, R. K. (International Journal of Environment, 2017)
About 198 sanitary workers work in Chandrapur Municipal Corporation, out of which 20 workers (10% of the population) was selected as a sample size (all male workers). The study was carried out from November 2015 to January 2016. Occupational health hazards of these workers were analyzed through questionnaire survey and Peak Expiratory Flow Rate (PEFR) analysis. The results of the study showed that, these workers were exposed to a number of environmental and occupational hazards leading to musculoskeletal disorders (85%), exposure to harmful gases (65%), respiratory problems (45%), headache (40%), dermatological problem (35%), gastrointestinal (10%) and leptospirosis (10%) during work. It was further observed that the workers were suffering from cough and cold (90%), skin problems (50%), allergies (15%), malaria and typhoid (15%), bronchitis lung and asthmatic problems (10%) and hearing disorder (5%) etc. after completion of work. The PEFR values were lower in exposed workers. Reduction in PEFR values was directly proportional with exposure duration. To reduce occupational health hazards, workers must be made alert and aware of potential health risk arising from their work. Reduction in exposure and use of personal protective equipments such as face mask, gloves, gum boots, caps, apron etc. should be encouraged.International Journal of EnvironmentVolume-6, Issue-3, Jun-Aug 2017, page: 15-24